Impact of Transformational Leadership on Work Motivation: Mediating Role of Procedural Justice - Uzair Ali; Saima Gul; Rana Aziz Ur Rehman; Dr. Adil Adnan (International Journal of Business and Economic Affairs, 2023)
Transformational leadership, work motivation, and procedural justice are getting increased attention because of their impact on business in terms of high productivity, job satisfaction, organizational commitment, higher performance, and many other related outcomes. In this study, we examined the direct and indirect impact of transformational leadership on work motivation. Procedural justice was used as a mediator to examine the indirect impact of transformational leadership on work motivation. A sample of 239 was taken from the whole population by using the convenience sampling technique. Data was collected from the respondents through standard questions. Regression analysis was used to find the hypothesized relationship. Results indicate that transformational leadership has a positive influence on work motivation and procedural justice partially mediates the relationship between transformational leadership and work motivation. Limitations of the study and future directions were also given. The study recommends that a transformational leadership style should be adopted by the management to enhance work motivation. This study will open a new avenue for scholars as well as practitioners.